Estrategias metodológicas para el desarrollo de las habilidades cognitivas en niños de 4 años del centro de desarrollo Infantil plastilina de Guayaquil durante el año 2016 - Centeno Delgado, María de los Ángeles (2016)
In this paper , I want to show the importance of using methodological strategies inearly childhood education focused on the development of cognitive skills, therefore,early childhood education is what allows to put the basis of the integral formation of human development and being also where the first skills and skills acquired,because this has been considered to create a guide of methodological strategies forteachers which will support and enhance the development of cognitive skills of 4years old children in the Child Development Center "Plastilina" of Guayaquil, as has been found that this institution in which exists poor development of cognitiveskills reflecting lack of agility of thought processes. The purpose of this proposal is to encourage teachers of early childhood educationto use the guide methodological strategies when teaching their classes logical relationship mathematics specifically, because it is where the estimulation of cognitive area is essential for troubleshooting, mental agility and logicalunderstanding…….